2021
DOI: 10.1161/jaha.120.019467
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Major Bleeding With Potent Antiplatelet Agents After an Acute Coronary Event: A Comparison of Ticagrelor and Clopidogrel in 5116 Consecutive Patients in Clinical Practice

Abstract: Background Major bleeding after acute coronary syndrome predicts a poor outcome but is challenging to define. The choice of antiplatelet influences bleeding risk. Methods and Results Major bleeding, subsequent myocardial infarction (MI), and all‐cause mortality to 1 year were compared in consecutive patients with acute coronary syndrome treated with clopidogrel (n=2491 between 2011 and 2013) and ticagrelor (n=2625 between 2012 and 2015) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Despite a sub-analysis from the Swedish Web-System for Enhancement and Development of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies (SWEDEHEART) registry, more bleeding occurred with ticagrelor than with clopidogrel, as in our study, when patients with a history of major bleeding, prior to hemorrhagic stroke, and those receiving dialyses were excluded from the analysis, no significant difference in the risk of bleeding was found between treatment groups ( 5 ). These findings should be put into perspective with those from recent studies, some of them indicating a reduction in MACE in favor of ticagrelor ( 5 , 16 , 30 , 31 ), others finding neither difference in mortality nor in MACE ( 7 11 , 28 ), with the overwhelming majority observing an increased risk of bleeding with ticagrelor vs. clopidogrel ( 5 11 ). Nonetheless, the underlying reasons for these contradictory results are still unclear.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Despite a sub-analysis from the Swedish Web-System for Enhancement and Development of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies (SWEDEHEART) registry, more bleeding occurred with ticagrelor than with clopidogrel, as in our study, when patients with a history of major bleeding, prior to hemorrhagic stroke, and those receiving dialyses were excluded from the analysis, no significant difference in the risk of bleeding was found between treatment groups ( 5 ). These findings should be put into perspective with those from recent studies, some of them indicating a reduction in MACE in favor of ticagrelor ( 5 , 16 , 30 , 31 ), others finding neither difference in mortality nor in MACE ( 7 11 , 28 ), with the overwhelming majority observing an increased risk of bleeding with ticagrelor vs. clopidogrel ( 5 11 ). Nonetheless, the underlying reasons for these contradictory results are still unclear.…”
Section: Discussionsupporting
confidence: 50%
“…Interestingly, among 66,870 patients included in 4 recent RCTs, the risk of premature discontinuation was 25% higher for ticagrelor-treated patients compared with those receiving the comparator (clopidogrel/placebo) ( 34 ). In view of the existing evidence, differential nonadherence with P2Y 12 inhibitors is a common threat in clinical practice, but as our study suggests, it should also be deemed as a potential source of selection bias to deal with in the observational studies based on the ITT principle ( 7 9 ). Nevertheless, despite the inherent limitations of ITT analysis in observational research, not enough attention has been paid to assessing the comparative safety and effectiveness of P2Y 12 inhibitors according to the on-treatment principle.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A large-scale retrospective cohort analysis has raised the concerns regarding increased risks of bleeding and dyspnea during ticagrelor versus clopidogrel treatment, which could lead to its early discontinuation ( 4 ). It was pointed out that the benefit of ticagrelor identified in a clinical trial may not be observed in a clinical practice ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is myocardial necrosis caused by acute and persistent ischemia and hypoxia of the coronary artery ( Liam et al, 2021 ). As the primary cardiovascular disease, AMI seriously affects health and life safety of human beings, which causes over 30% mortality of coronary heart disease patients ( Blais et al, 2020 ; Thomas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%